Evaluation of modal pushover analysis using generic frames. - Chintanapakdee, Chatpan
The recently developed modal pushover analysis (MPA) has been shown to be a significant improvement over the pushover analysis procedures currently used in structural engineering practice. None of the current invariant force distributions accounts for the contribution of higher modes-higher than the fundamental mode-to the response or for redistribution of inertial forces because of structural yielding. By including the contributions of a sufficient number of modes of vibration (generally two to three), the height wise distribution of responses estimated by MPA is generally similar to the 'exact' results from non linear response history analysis (RHA). Although the results of the previous research were extremely promising, only a few buildings were evaluated. The results presented below evaluate the accuracy of MPA for a wide range of buildings and ground motion ensembles. The selected structures are idealized frames of six different heights : 3, 6, 9, 12, 15 and 18 stories and five strength levels corresponding to SDF system ductility factor of 1, 1.5, 2, 4 and 6; each frame is analysed for 20 ground motions. Comparing the median values of storey drift demands determined by MPA to those obtained from non-linear RHA shows that the MPA predicts reasonably well the changing height wise variation of demand with building height and SDF system ductility factor. Median and dispersion values of the ratios of storey drift demands determined by MPA and non linear RHA procedures were computed to measure the bias and dispersion of MPA estimates with the following results : (1) the bias and dispersion in the MPA procedure tend to increase for longer period frames and larger SDF system ductility factors (although these trends are not perfect); (2) the bias and dispersion in MPA estimates of seismic demands for inelastic frames are usually larger than for elastic systems; (3) the well known response spectrum analysis (RSA), which is equivalent to the MPA for elastic systems, consistently underestimates the response of elastic structures, e.g. up to 18 percent in the upper storey drifts of 18 storey frames. Finally, the MPA procedure is simplified to facilitate its implementation in engineering practice-where the earthquake hazard is usually defined in terms of a median (or some other percentile) design spectrum for elastic systems- and the accuracy of this simplified procedure is documented.
Keywords: Building design; Building evaluation; Non-linear static procedure; Pushover analysis; Seismic demands